2017
DOI: 10.1044/2016_jslhr-h-16-0184
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sound-Processor Threshold Levels for Pediatric Cochlear Implant Recipients Using Conditioned Play Audiometry via Telepractice

Abstract: Purpose: This study evaluated the use of telepractice for measuring cochlear implant (CI) behavioral threshold ( T) levels in children using conditioned play audiometry (CPA). The goals were to determine whether (a) T levels measured via telepractice were not significantly different from those obtained in person, (b) response probability differed between remote and in-person conditions, and (c) the remote visit required more time than the in-person condition. Method: An ABBA design (A, in-person; B, remote) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 14 publications
2
31
1
Order By: Relevance
“…This study used the same design as reported by Goehring and Hughes (2017) for the older children tested using CPA. An AB-BA design was used, with each pair of sessions typically spaced over two visits.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study used the same design as reported by Goehring and Hughes (2017) for the older children tested using CPA. An AB-BA design was used, with each pair of sessions typically spaced over two visits.…”
Section: Methodsmentioning
confidence: 99%
“…Because the procedures used to set upper comfort levels are more subjective and can vary widely across clinicians, we chose to focus on T levels as the primary outcome measure for this study. In accordance with our earlier study (Goehring & Hughes, 2017), we also evaluated test time and measurement success rate for the two test conditions, as well as questionnaire responses from caregivers that rated the acceptance and usability of remote programming. The null hypothesis was that there would be no significant differences in T levels, test time, or measurement success rate between the in-person and remote conditions.…”
mentioning
confidence: 92%
See 3 more Smart Citations